Prescription patterns and therapeutic gaps among persons with epilepsy in Southwestern Nigeria - Ogunjimi, Luqman; Osalusi, Bamidele; Fagbemi, Ayotomiwa; Oyenuga, Ibironke; Ojini, Fedora; Collins, Samuel; Elegbede, Oluwatosin; Oladele, Olayinka; Fehintola, Fatai (Frontiers in Pharmacology, 2024)
Pharmacotherapy with Anti-Seizure Medications (ASMs) remains the cornerstone of achieving long-term remission in People with Epilepsy (PWE). The study aims to determine the prescription pattern and Therapeutic Gaps (TG) among PWE. This descriptive, cross-sectional study recruited 940 PWE aged ≥18 years, with a clinically confirmed diagnosis of epilepsy using the International League Against Epilepsy (ILAE) criteria. At a scheduled interview with each participant, a previously established questionnaire was used to obtain clinical information relating to epilepsy with regard to the age of onset, etiology, duration of epilepsy, frequency, types, and number of ASM used. There were fewer male participants (445 (47.4% ) vs 495 (53.6 %), and higher mean age of onset (35.19±21.10 vs. 31.58±20.82; p0.009) compared to females. The medication characteristics showed that 336(35.7% ) of the 940 epilepsy patients recruited were not on ASM, while 604 (64.3% ) patients were on ASM, with 504 (83.4% ) on monotherapy vs 100 (16.6% ) on polytherapy. There was higher mean age [40.92±19.40 vs 33.61±16.51; p<0.001], and higher mean age of onset [34.47±21.80 vs 25.39±19.78; p<0.001] in PWE on ASM monotherapy compared to those on polytherapy. Furthermore, there was higher number of participants on ASM monotherapy among participants with seizure duration <2 years [251( 87.5 % ) vs 36 (12.5% )] and seizure duration > 2 years [253 (79.8% ) vs. 64 (20.2% )]. The majority of participants on ASM were on monotherapy, with CBZ being the most frequently prescribed medication. Furthermore, about a third of participants had TG in PWE. Healthcare providers should focus on alleviating the TG among PWE.